Konsep Dasar Pertumbuhan Dan Perkembangan Terhadap Kematangan Belajar di TK Sehat - Aang Andi Kuswandi; Sinka Nurussalam; Rifka Ainunida (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
Growth iiand iidevelopment iihave iithe iisame iimeaning, iithat iiis, iiboth iiexperience change, iibut iispecifically iithe iiterm iigrowth iiis iidifferent iifrom iidevelopment. Growth iiis iibiological, iianatomical iiand iiphysiological iichanges iiin iihumans, while iidevelopment iiis iipsychological iiand iimotoric iichanges iiin iihumans. Students iiare iicreatures iithat iigrow iiand iidevelop. iiDevelopment iiis iia iinatural process iithat iievery iiindividual iifaces. iiIn iithis iicase iistudents iidevelop iithe potential iithat iiexists iiwithin iithem iithrough iithe iiprocess iiof iilearning iiand education. iiThis iilearning iiis iitaken iiin iiseveral iilevels, iistarting iifrom iithe earlyischool iiage iito iithe iimiddle iilevel. iiStudent iidevelopment iiis iian iiimportant component iithat iimust iibe iiknown iiby iian iieducator iior iiteacher. iiEducators' understanding iiof iistudent iidevelopment iiwill iihelp iieducators iiin iithe iilearning process. iiEducators iican iichoose iiwhat iikind iiof iitheme iiis iiin iiaccordance iiwith the iidevelopment iiof iistudents. iiLearning iithat iidoes iinot iipay iiattention iito iithe development iiof iiparticipants iiwill iimake iiparticipants iibored iiand iifrustrated.